1963
DOI: 10.1002/jcp.1030620210
|View full text |Cite
|
Sign up to set email alerts
|

The localization and effects of mercury bound by the surviving frog skin

Abstract: The dependence of the spontaneous potential across the surviving frog skin in sodium-containing media on the active transport of sodium across the skin in the inward direction has been unequivocally demonstrated by a number of authors (see, e.g. Koefoed-Johnsen and Ussing, '60, for references). A number of substances inhibiting the active transport of sodium across the skin and thus bringing about a drop in the spontaneous potential across the skin toward zero are known; among these, mercuric chloride is noted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1969
1969
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The inhibition of SCC produced by equimolar addition of cysteine and Cd § § to the apical Ringer's is similar to results obtained by Linderholm (1952) and Lodin et al (1963), who found 10-4M HgC12 alone to inhibit SCC when added to the apical surface of isolated Rana temporaria skin. Using the method of Steinbach (1933), Lodin et al (1963 found that this inhibition of SCC by Hg ++ treatment was associated with an increase in the resistance of the morphologically outer barrier of the epithelium with little or no effect on the inner barrier.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The inhibition of SCC produced by equimolar addition of cysteine and Cd § § to the apical Ringer's is similar to results obtained by Linderholm (1952) and Lodin et al (1963), who found 10-4M HgC12 alone to inhibit SCC when added to the apical surface of isolated Rana temporaria skin. Using the method of Steinbach (1933), Lodin et al (1963 found that this inhibition of SCC by Hg ++ treatment was associated with an increase in the resistance of the morphologically outer barrier of the epithelium with little or no effect on the inner barrier.…”
Section: Discussionsupporting
confidence: 88%
“…It would appear, then, that divalent metals can inhibit SCC by either reducing passive entry into epithelial cells, as Lodin et al (1963) observed for Hg + § or by directly inhibiting the active transport mechanism of the basal-lateral membranes, as observed with the bladder and large intestine. Furthermore, the presence of a carrier, such as cysteine or metallothionein, can modify the response at either site of action.…”
Section: Discussionmentioning
confidence: 87%
“…These studies revealed : (a) that several methionine analogues and derivatives are equally effective, and (b) that a reversible breakdown of a part of cerebral polyribosomes to monoand dimeric ribosomes coincident with a transient stimulation of cerebral protein synthesis accompanies, and possibly mediates the seizure-protective action of methionine (SELLINGER and AZCURRA, 1970). LODIN and his co-workers (LODIN, FALTIN, PILNY and HARTMAN, 1968;LODIN, MULLER and FALTIN, 1968) have also recently described effects of MSO on nucleic acids and proteins in neural tissue. Previously the intracellular disposition of MSO in brain had been examined only cursorily ( LAMAR and SELLINGER, 1965;DE ROBERTIS et al, 1967), mainly because MSO of sufficiently high specific radioactivity was unavailable.…”
mentioning
confidence: 99%